Epidural analgesia after minimally invasive esophagectomy: efficacy and complication profile. Issue 8 (17th December 2018) - Kingma, B F; Visser, E; Marsman, M; Ruurda, J P; van Hillegersberg, R
SUMMARY: Adequate postoperative pain management is essential to facilitate uneventful recovery after esophagectomy. Although epidural analgesia is the gold standard, it is not satisfactory in all patients. The aim of this study is to describe the efficacy and complication profile of epidural analgesia after minimally invasive esophagectomy (MIE). A total of 108 patients who underwent a robot-assisted (McKeown) MIE for esophageal cancer were included from a single center prospective database (2012–2015). The number of patients that could receive epidural analgesia, the sensory block range per day, the number of epidural top-ups, the need for escape pain mediation (i.e. intravenous opioids), the highest pain score per day (numeric rating scale: 0–10), and epidural-related complications were assessed until postoperative day (POD) 4. Epidural catheter placement was achieved in 101 patients (94%). A complete sensory block was found in 49% (POD1), 42% (POD 2), 20% (POD3), and 30% (POD4) of patients. An epidural top-up was performed in 26 patients (24%), which was successful in 22 patients. Escape pain medication in the form of intravenous opioids was given at least once in 49 out of 108 patients (45%) on POD 1, 2, 3, or 4. Overall median highest pain scores on the corresponding days were 2.0 (range: 0–10), 3.5 (range: 0–9), 3.0 (range: 0–8), and 4.0 (range: 0–9). Epidural related complications occurred in 20 patients (19%) and included catheter problems ( n  = 11), hypotension ( n  = 6), bradypnea ( n  = 2), and reversible tingling in the legs ( n  = 1). In conclusion, in this study epidural analgesia was insufficient and escape pain medication was necessary in nearly half of patients undergoing MIE.